336 ASYMPTOMATIC ORTHOSTATIC HYPOTENSION AND RISK OF FALLS IN COMMUNITY-DWELLING OLDER PEOPLE. (25th October 2022) - Claffey, P; Pérez-Denia, L; Lavan, A; Kenny, RA; Finucane, C; Briggs, R
Abstract: Background: Many older people with Orthostatic Hypotension (OH) may not report typical symptoms of dizziness, light-headedness, or unsteadiness. However, the relationships between OH and falls in the absence of typical symptoms are not yet established. Methods: Continuous orthostatic BP was measured during active stand using a Finometer at Wave 1 of TILDA in participants aged≥70 years. OH, with and without dizziness, was defined as a sustained drop in systolic BP≥20 and/or diastolic BP≥10 mm Hg at 30, 60 and 90 seconds post-standing. The association between symptoms of dizziness and orthostatic BP was assessed with multi-level mixed-effects linear regression; logistic regression models assessed the longitudinal relationship between OH and falls at 6-year follow-up (Waves 2-5). Results: Almost 11% (n=934; mean age: 75 years; 51% female) had OH, two-thirds of whom were asymptomatic. Dizziness was not associated with systolic BP drop at 30 (β=1.54; –1.27, 4.36; p=0.256), 60 (β=2.6; –0.19, 5.47; p =0.476) or 90 (β=2.02; –0.91, 4.95; p=0.176) seconds after standing in adjusted models. Asymptomatic OH was independently associated with unexplained falls (Odds Ratio: 2.01; 1.11, 3.65; p=0.022) but not explained falls (OR 0.93; 0.53, 1.62; p=0.797) during follow-up. Conclusion: Two-thirds of older people with OH did not report typical symptoms of light-headedness. Dizziness or unsteadiness after standing did not correlate with the degree of orthostatic BP drop or recovery. Participants with asymptomatic OH had a significantly higher risk of unexplained falls during follow-up, and this has important clinical implications for the assessment of older people with falls.